2021
DOI: 10.21203/rs.3.rs-705699/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic Nexus Among CO2 Emissions, Fossil Energy Usage and Human Development in East Africa: New Insight From Novel DARDL Simulations

Abstract: This study investigates the relationship among CO2 emissions, human development index, and fossil energy usage. Essentially, the study was informed by the Sustainable Development Goal 7, which stipulates universal access to renewable and contemporary energy technologies. We employed the novel dynamic autoregressive-distributed lag (DARDL) simulations with a dataset spanning between1980 and 2020 from East Africa Community (EAC). The study revealed that human development, access to electricity, and trade have a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…By adopting qualitative technique, Biswas (2020) showed that environmental literacy and attitude are major predictors of a healthy lifestyle in an emerging economy. Dumor et al (2021) applied the dynamic ARDL approach for a study on East African countries and found that increase in HDI, has no significant effect on carbon emissions both in the short and long term.…”
Section: The Win-win Studiesmentioning
confidence: 99%
“…By adopting qualitative technique, Biswas (2020) showed that environmental literacy and attitude are major predictors of a healthy lifestyle in an emerging economy. Dumor et al (2021) applied the dynamic ARDL approach for a study on East African countries and found that increase in HDI, has no significant effect on carbon emissions both in the short and long term.…”
Section: The Win-win Studiesmentioning
confidence: 99%